Pengaruh Teknik Peta Konsep dan Minat Membaca Karya Sastra terhadap Kemampuan Menulis Narasi - Muhammad Ihsan; Lalu Awaluddin (FONDATIA, 2018)
The study was conducted in order to find out the implementation of concept mapping technique and interest in reading literary works towards narrative writing ability of the students at class V SDN.7 Pedungan Denpasar. The problems of the study involved : ( 1 ) Was there any different narrative writing ability of students joining concept mapping technique instructional model ? (2) Was there any differernt narrative writing ability between the students having high interest in reading literary works with those having low interest in reading literary works ? (3) Was there any contributive interaction between concept mapping technique with interest in the reading literary works towards narrative writing ability ? (4) Was there any different narrative writing ability of students joining concept mapping technique instruction with others joining a conventional instructional model among the students having high interest in reading literary works ? (5) Was there any different narrative writing ability of the students joining concept mapping technique instruction with others joining a conventional instructional model among the students having low interest in reading literary works